Relationship between Shift Work and Cardiovascular disease Risk Factors in workers referred to Occupational Medicine Center of Gonabad University of Medical Sciences - maryam Moaven Saeidi; Mohsen Saheban Maleki; Behnam Mazlum (Caspian Journal of Health Research, 2022)
Background: There are many well-known biologic and anthropometric risk factor for developing cardiovascular diseases (CVD). Shift work (SW) may be associated with CVD risk factors. Objectives: This study was performed to investigate the relationship of shift work and some of CVD risk factors. Materials & Methods: This analytical cross-sectional study was done in Occupational Medicine Center of Gonabad University of Medical Sciences from April to December in 2021. A total of 743 workers who referred for periodic health examination were selected by simple random sampling. Those workers with at least one year of work experience who had Satisfaction for participation were included to the study. Having congenital heart disease, heart failure, kidney disease, Taking drugs that increase blood pressure, blood lipid and sugar and pregnant women were excluded.  Demographic data, Physical examination and Blood cholesterol, triglyceride and glucose measures were collected. Data analysis was performed using Mann–Whitney U test, student t-test, Chi-Square and Multivariate Linear Regression model with SPSS software version 21 at a significant level of 0.05. Results: Of total, 73.4% were men and 47.3% were shift workers. The mean (Standard Deviation) of age was 33.9 (5.07) among shift workers, and 36.32 (5.81) among Day-time workers. There was significant independent association between shift work and triglyceride (B=7.5, 95%CI=1.02,1.21, P=0.03) and cholesterol (B=7.2, 95%CI=1.12,1.22, P=0.028) values. Conclusion: The results of the present study showed that the concentration of blood triglycerides and cholesterol is higher in shift workers than day-time workers. Therefore, particular follow-up of shift workers should be recommended for screening and preventing cardiovascular risk factors